Online Education: the Academic Impact and Learning Effects - Mahamad, Saipunidzam; Sobri Hashim, Ahmad; ., . (International Journal of Engineering and Technology, 2018)
Online education is a new way of learning which simplified many factors that affect student intake in higher institution. It gives opportunity to increase the level of education with or without going to the institution. Even though, there is an abundance of research pertaining to online education but very few of these research studies focus on the academic impact and learning effects of this modality on students. These paper present a review on academic impact and learning effects of online education. Educators and learners are benefited to explore beyond traditional classroom in many ways including development of technologies, social contribution and pedagogical.Â Â